Spectral theory of large dimensional random matrices and its applications to wireless communications and finance statistics : random matrix theory and its applications - Bai, Zhidong; Fang, Zhaoben; Liang, Ying-Chang (University of Science and Technology of China Press ; World Scientific, 2014)
The book contains three parts: Spectral theory of large dimensional random matrices; Applications to wireless communications; and Applications to finance. In the first part, we introduce some basic theorems of spectral analysis of large dimensional random matrices that are obtained under finite moment conditions, such as the limiting spectral distributions of Wigner matrix and that of large dimensional sample covariance matrix, limits of extreme eigenvalues, and the central limit theorems for linear spectral statistics. In the second part, we introduce some basic examples of applications of ...